Penanaman Moral Pada Anak Melalui Ibadah Shalat Dhuha - Ubabuddin, Ubabuddin (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2018)
Moral is sensitivity in thoughts, feelings and actions that do not only include sensitivity to principles and rules. Moral includes the ability of a person to distinguish between right and wrong actions, morality becomes the basic basis in attitude. Moral cultivation for children and participants is a matter of positive moral development efforts because it will become the habit of students in conditions in accordance with good qualities in a family environment or wider community group, can be done by habituation, exemplary, and advice . Planting moral and religious values that must be instilled in children is the role of Dhuha prayer worship. In carrying out the Dhuha prayer activities, the family environment and environment can be used to enforce Dhuha prayer. Before the implementation of the Dhuha prayer the children did to take the air in an orderly manner, purify from the hadats, wear holy clothes, and teach discipline.